FORMULASI TABLET EFFERVESCENT EKSTRAK DAUN SINGKONG (Manihot utillissima Pohl.) DAN EKSTRAK HERBA PEGAGAN (Centella asiatica (L.) Urban) - Serevino L. Ambuk; Agatha Budi Susiana Lestari (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2012)
Abstract: Asiaticoside compound in gotu kola extract (Centella asiatica (L.) Urban) and rutincompound in extract of cassava leaves (Manihot utillissima Pohl.) has been proofed fordegenerative diseases treatment. Effervescent tablet was chosen to facilitate the herb gotu kolaextract and cassava leaves extract because of fresh sensation and easy to use. The aims of thisstudy was investigated the effect of tartaric acid, sodium bicarbonate, their interactions, anddiscovered the optimum composition in order to producing effervescent tablets for qualityrequirements. Quality requirements term in this study were the moisture content of granule, tablethardness, friability of tablets, dissolution time. The results showed that tartaric acid significantlyinfluenced moisture content of granules, tablets friability, dissolution time of tablets, whilesodium bicarbonate significantly affected tablets hardness. Based on super imposed contourplot, the optimum composition for effervescent tablets was at the level 1000 mg tartaric acid and1120 mg sodium bicarbonate.Keywords: gotu kola extract, cassava leaves extract, effervescent tablet